Ecology of Sonoran Desert Plants and Plant Communities - Robichaux, Robert Hall (Book collections on Project MUSE., 1999)
This book offers an accessible introduction to Sonoran Desert ecology. Eight original essays by Sonoran Desert specialists provide an overview of the practice of ecology at landscape, community, and organism levels. The essays explore the rich diversity of plant life in the Sonoran Desert and the ecological patterns and processes that underlie it. They also reveal the history and scientific legacy of the Desert Laboratory in Tucson, which has conducted research on the Sonoran Desert since 1903.